Colossal thermopower, spin states and delocalization effects in single layered La2−xSrxCoO4. (15th August 2017) - Ahad, Abdul; Shukla, D.K.; Rahman, F.; Majid, S.; Tarachand; Okram, G.S.; Sinha, A.K.; Phase, D.M.
Abstract: Hole-doped La2 CoO4 compounds have been widely studied due to their multifaceted behavior such as charge ordering, spin ordering and spin blockade. Hole doping in La2 CoO4 causes appearance of the Co 3+ along with the Co 2+, which makes it an interesting model system for study of the spin-state transitions. In hole-doped samples, the spin-states of the Co 3+ ions at large have been reported as the low or intermediate state. We report here a study on the Sr doping in La2 CoO4 . The Sr doping has been found to stabilize the crystal structure. By combining structural, electronic structure and electrical transport results, it is observed that the high-spin state is present in all the La2− x Sr x CoO4 (x = 0.5, 0.8, 0.9 and 1.0) samples. The high-spin state has been found to be concomitant with the delocalization of the e g electrons. In addition, in these materials, a colossal thermopower has been observed for first time in the cryogenic temperatures. Graphical abstract: Figure 1 (a) The Co L3, 2 edges XAS spectra of all samples under investigation together with the Co3 O4 as reference. EuCoO3 : Co 3+ LS, Sr2 CoO3 Cl: Co 3+ HS and CoO: Co 2+ HS (b) The simulated Co L3, 2 edge XAS spectra of all the compositions together with the simulated Co 3+ HS, Co 3+ LS and Co 2+ HS spectra. Figure 2. Fitted (continuous curves) thermopower curves. Symbols are experimental data points. Three different regions A, B and C are fitted with three different models. Image 1